Effect of WSP, a Chinese Herbal Formula, on Th17/Treg Ratio and HBeAg Seroconversion in Telbivudine-Treated HBeAg-Positive Chronic Hepatitis B Patients with High Baseline ALT Levels (20–30 Times the ULN). (5th March 2019) - Zhang, Yang; Wang, Yi-Tong; Luo, Jian-Xing; Hu, Xiao-Yu; Yang, Fang; Lin, Wu; Liang, Xiao; Zhao, Bing-Jie; Zhang, Song; Chen, Yuan-Yuan
Abstract : Chronic hepatitis B (CHB) is a global health problem. Clinically, many patients have baseline alanine aminotransferase (ALT) levels above 20 times the upper limit of normal (ULN), but there are few reports about these patients. The prospective randomized placebo-controlled clinical study was designed to investigate the effect of WSP, a Chinese herbal formula, on telbivudine- (LDT-) treated HBeAg-positive CHB patients with high baseline ALT levels (20–30 times the ULN) and kidney-yang deficiency syndrome. Eligible patients were randomized to receive LDT 600 mg/day in combination with WSP (treatment group) or placebo granules (control group) 16.28 g/day for 52 weeks. The results showed that HBeAg seroconversion (SC) rate (44.1%) in the treatment group ( n =34) was significantly superior to that (20.6%) in the control group ( n =34) at 52 weeks ( P < 0.05). Meanwhile, WSP could promote HBV DNA negative conversion (85.3% versus 61.8%, P < 0.05) and ALT normalization (94.1% versus 76.5%, P < 0.05) compared with the placebo. There were no drug-related serious adverse events. During the treatment, the peripheral blood Th17/Treg ratio first increased and then decreased in the treatment group and reached the peak at 12 weeks ( P < 0.05). At 12, 24, 36, and 52 weeks, Th17/Treg ratio in the treatment group was better than those in the control group (all P < 0.05). In addition, the patients ( n =22) with HBeAg SC had higher Th17/Treg ratio than the patients ( n =46) without SC at 12 weeks (0.68±0.26 versus 0.43±0.18, P < 0.001). In conclusion, WSP could safely enhance HBeAg SC and promote HBV DNA negative conversion and ALT normalization in LDT-treated HBeAg-positive CHB patients with high baseline ALT levels (20–30 times the ULN) and kidney-yang deficiency syndrome. Th17/Treg ratio was not only related to the mechanisms of WSP but also a good predictor of 52-week HBeAg SC.